India's Total Natural Resource Rents (NRR) and GDP: An Augmented Autoregressive Distributed Lag (ARDL) bound test - Sanjay Taneja; Mukul Bhatnagar; Pawan Kumar; Ramona Rupeika-Apoga (Journal of Risk and Financial Management, 2023)
Utilizing natural resources wisely, reducing pollution, and taking other environmental factors into account are now critical to the prospects for long-term economic growth and, by extension, sustainable development. We investigate the impact of total natural resource rents (NRR) on India's GDP in this study. The data sample consists of NRR and GDP data from the World Bank's official website collected between 1993 and 2020. In the study, the Granger causality test and an augmented autoregressive distributed lag (ARDL) bound test were used. The NNR have a significant impact on India's GDP, according to the results of the ARDL model on the framed time series data set. Furthermore, the ARDL bound test reveals that the NRR have a significant short-term and long-term impact on the GDP of the Indian economy. This research contributes to understanding whether an exclusive policy is required for effective management of the complex interactions between various forces in the economic, political, and social environments. This is significant because there is no standard policy in India to improve the efficiency of utility extraction from natural resources.
Keywords: 650; India; sustainable development; ARDL bound test; GDP; total natural resource rents